The Development of Formal Ceremonial Coronation Attire of Seri Paduka Baginda yang di-Pertuan Agong From I-XIV Starting From 1957 until 2016 - Nor Idayu binti Ibrahim (IJCAS (International Journal of Creative and Arts Studies), 2016)
There is specific formal attire wear by “Seri Paduka Baginda Yang di-Pertuan Agong”. The exploration related with Malaysia royal institution and royal etiquettes are aspiring, interesting and there are numbers of printed publications had discovered in depth, onto this fields. Unfortunately, most of them have not yet discovered in-depth research about the development of formal ceremonial coronation attire of “Seri Paduka Baginda Yang diPertuan Agong”. The purpose of this paper is to discover the development of ceremonial coronation attire and to document the knowledge regarding the research paper topic. Meyer Schapiro theory of style is used in this research equivalent to feature its style and design of the ceremonial coronation attire. Method applied was the qualitative method because it is the suitable approach to gathering valid data from the experience experts. It is also discussed on the style, muskat and the design of ceremonial attires of them. The coronation attire also known as Royal Regalia. The items are Tengkolok di-Raja, Pending di- Raja, Short Keris and Long Keris. Finally, this research hopefully will benefit and provide a vital source of references to the Malay civilization, researchers, academicians, scholars, students, cultural activist, and also Malaysian regarding with the formal coronation ceremonial attire of “Seri Paduka Baginda Yang di- Pertuan Agong” especially back dated during the period of 1957 until 2016.